Turkish Version of Cognitive Behavioural Avoidance Scale: Psychometric Properties and Psychopathological Correlates - Selmin Erdi-Gok; Ozden Yalcinkaya Alkar (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
The present study examined the psychometric properties of the Turkish version of Cognitive Behavioural Avoidance Scale (CBAS-TR) in a sample of 330 Turkish university students. The CBAS assesses people's tendency toward several dimensions of avoidance. The reliability and validity analyses of the Turkish version of the scale indicated that the CBAS-TR had adequate psychometric properties and it is a reliable and valid measure that can be employed in Turkey. Internal consistency (Cronbachs α = .92) and test-retest reliability (α = .87, r = .66, ICC = .86) scores were satisfactory. Concurrent validity studies on CBAS-TR indicated significant correlations with depression, anxiety, tolerance to distress, psychological inflexibility, and suppression. Consistent with the original CBAS, factor analysis of CBAS-TR identified four components (i.e. Cognitive Social Avoidance, Behavioural Social Avoidance, Cognitive Nonsocial Avoidance, and Behavioural Nonsocial Avoidance) that accounted for 46.8% of the total variance. There was a divergence from the original form of CBAS, only for one item (i.e. item 28) which was loaded to a different factor (i.e. to "Behavioural Social Avoidance", and not to "Behavioural Nonsocial Avoidance") in the present study. Possible contributors to this finding were suggested. Lastly, avoidance tendencies and avoidance strategy types of participants with low and high levels of depression and anxiety were compared; group differences were discussed. [JCBPR 2019; 8(1.000): 16-24]